The Effect Promotion E- Commerce Toward Effectiveness Promotion By Using (AIDA) Methods - Nurvi Oktiani; Kartika Yuliantari; Taat Kuspriyono; Haryani Haryani; Rani Kurniasari (Universitas Bina Sarana Informatika, 2022)
Adpers-art communities is one of community have been built by similarity of hobbies, which is consist of making artworks in paper media or others which have three dimension. This research used quantitative method by multiply analysis regression, the sample from this research include 57 of consumer, the analysis data use reliability test, validity test, multicollinearity, Heteroscedasticity, Autocorrelation, normality, regression test. The Purpose of this research are known, the effect promotion E- Commerce toward effectiveness promotion by using AIDA Methods for Adpers – Art Community Product. For result, it can be described the regression model are significant for measuring percentage from dependent variable and change independent variable every 1%, coefficient regression from attention :3.28, interest 6.43, desire : 3.324 as much can make increase effectiveness promotion, and Action :3.309 as much give effect for increasing effectiveness promotion , in advice, Adpers Art Community must think of about how to improve attention, desire and action from consumer with any strategy for example increasing the effectiveness promotion by website and make specify strategies for improve especially attention, desire and action from consumer